METODA PENGHILANGAN LOGAM BERAT (As, Cd, Cr, Ag, Cu, Pb, Ni dan Zn) DI DALAM AIR LIMBAH INDUSTRI - Said, Nusa Idaman (Center for Environmental Technology, 2010)
Industry is a potential source of water pollution, it produces pollutants that are extremely harmful to people and the environment. Many industrial facilities use freshwater to carry away waste from the plant and into rivers, lakes and oceans. Inorganic industrial wastes are more difficult to control and potentially more hazardous Industries discharge a variety of toxic compounds and heavy metals. The most pollutans heavy metals are Lead, Cadmium, Copper, Chromium, Selenium, Mercury, Nickel, Zinc, Arsen and Chromium. Heavy metals are dangerous because they tend to bioaccumulate. Mercury for example, causes damages to the brain and the central nervous system, causes psychological changes and makes development changes in young children. Normally Mercury is a toxic substance which has no known function in human biochemistry.There are several methods to eliminate or remove heavy metals in water such as chemical oxidation process, ion exchange process, adsorption process, an electrochemical process, reverse osmosis process and other alternative methods likes biosorption. Each method has strengths and weaknesses, therefore to choose the method of removing heavy metals in wastewater depending on pollutants conditions such as concentrations of heavy metals in wastewater, types of heavy metal, heavy metal concentrations in treated water, land availability, flow rate of wastewater will be processed and other parameters. In this paper discusses several methods of removal of heavy metals in industrial wastewater such as chemical precipitation and oxidation processes, adsorption and ion exchange process.Ã‚Â Keywords : water pollution, heavy metal, industrial wastewater, removal methods